Bio-inspired functionalization of PA1012 into piezoelectric ionomers via molecular asymmetry and ion-cluster polarization - Guangmou Cao; Rong Li; Qi Liang; Jingwen Liu; Pengyuan Luo; Haomeng Ma; Yang Yu; Linyi Cui; Le Xu; Jingjing Ma; Tong Lin; Liuchun Zheng (Chemical Engineering Journal, 2026)

Larix gmelinii UGPase enhances vegetative growth in transgenic poplar through an HYH-mediated positive feedback loop - Xin Guo; Linyi Zhang; Zhuo Zhao; Jiaqi Wang; Lili Mei; Renhua Ji; Tuoya; Xiaofei Lin (Plant Cell Reports, 2026)

A transformer-reinforcement learning framework integrating acoustic thermometry for multi-pollutant prediction and control in a full-scale WtE plant in China - Yuxuan Ying; Linyi Chen; Hanqing Yang; Tianyi Zhu; Weiwei Cao; Zhenwei Yang; Hongyu Sun; Jinghao Ye; Yu Liu; Yunhua Zhao; Weiya Jin; Mi Yan; et al. (Journal of Cleaner Production, 2026)

Characteristics of Extratropical Cyclones and Associated Precipitation Across the Huang‐Huai River Basin, East China - Zhiqiang Lin; Long Jiang; Xiuping Yao; Linyi Lyu; Ke Li; Caiyun Feng (International Journal of Climatology, 2026)
The Huang‐Huai River Basin (HHRB) in East China is highly susceptible to frequent floods and droughts, making it one of the most disaster‐prone regions in China. Extratropical cyclones (ETCs) are the primary weather systems generating precipitation over the HHRB. This study investigates the spatiotemporal characteristics and precipitation patterns of ETCs affecting the HHRB, based on a long‐term dataset (1979–2022) derived from ERA5 reanalysis. On average, 33.2 ETCs traverse the HHRB annually, exhibiting a statistically insignificant increasing trend over the study period. Most ETC activity occurs during summer months and nighttime hours. ETCs contribute to approximately 60% of the HHRB's total precipitation, with their contribution increasing for more intense precipitation events. Based on source regions and tracks, the ETCs are classified into five distinct types: locally generated systems and those originating from northwestern, northeastern, southwestern, and southern China. Locally generated ETCs produce the largest total precipitation, whereas those originating from southwestern China trigger the most intense rainfall events. ETC‐induced precipitation plays a crucial role in driving summer floods and droughts over the HHRB. Consequently, a deeper understanding of the characteristics, formation mechanisms, and precipitation‐generating processes of these systems is essential for effective disaster prevention and mitigation strategies.

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Risk assessment of potentially toxic elements, microplastics, and microorganisms in groundwater around municipal solid waste landfill - Xueya Li; Tianmu Peng; Linyi Lin; Muhammad Amjad Khan; Shurui Zhang; Meijuan Kuang; Jinming Lou; Jiaxin He; Pangxiang Zhang; Xiaomao Song; Xu Wang; Qing Huang (Journal of Hazardous Materials, 2025)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Application of heavy metal immobilization in soil by biochar using machine learning - Genmao Guo; Linyi Lin; Fangming Jin; Ondřej Mašek; Qing Huang (Environmental Research, 2023)